Budaya Madrasah dan Pembentukan Karakter Peduli Lingkungan di MIN 2 Kota Palembang - Widiawaty; Abdullah Idi; Karoma; Yulia Tri Samiha (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to analyze madrasah culture and the formation of students’ environmental care character through the Adiwiyata Program at MIN 2 Kota Palembang from the perspective of Islamic educational sociology. This study employed a qualitative approach with a case study design. Data were collected through semi-structured interviews, observation, and documentation involving the head of madrasah, teachers, the Adiwiyata team, students, and relevant school personnel. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The findings reveal three main points. First, the Adiwiyata Program has been institutionalized as part of madrasah culture through environmental policies, curriculum integration, participatory activities, environmentally friendly facilities, and regular evaluation. Second, teachers play a central role as agents of value socialization through exemplary behavior and repeated habituation, such as classroom cleaning duties, waste collection, recycling activities, and plant care. Third, students’ environmental care character begins to develop from obedience to teachers’ instructions into social awareness, shown through keeping the classroom clean, disposing of waste properly, caring for plants, and reminding peers. However, this internalization still faces challenges, including inconsistent home habituation, peer influence, consumptive habits, waste volume, and limited supporting facilities. This study contributes to strengthening environmental character education in madrasah by showing that environmental care is formed not only through formal programs, but also through institutionalized culture, teacher role modeling, collective habituation, and sustainable social practices.